2016
DOI: 10.1016/j.cell.2016.11.052
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Amelioration of Age-Associated Hallmarks by Partial Reprogramming

Abstract: SUMMARY Aging is the major risk factor for many human diseases. In vitro studies have demonstrated that cellular reprogramming to pluripotency reverses cellular age, but alteration of the aging process through reprogramming has not been directly demonstrated in vivo. Here, we report that partial reprogramming by short-term cyclic expression of Oct4, Sox2, Klf4, and c-Myc (OSKM) ameliorates cellular and physiological hallmarks of aging and prolongs lifespan in a mouse model of premature aging. Similarly, expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
734
6
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 679 publications
(793 citation statements)
references
References 58 publications
32
734
6
21
Order By: Relevance
“…Here, we underscored the potential of therapeutic elimination of senescent cells, for instance by FOXO4-DRI. In addition, exciting developments were recently reported in the field of stem cell biology, where it was shown that transient expression of the Yamanaka stem cell factors can promote tissue rejuvenation [7]. This is not yet therapeutically applicable, but most likely this will only be a matter of time.…”
Section: Le Tour De Foxo a Demanding Journey But One With Great Rewmentioning
confidence: 99%
“…Here, we underscored the potential of therapeutic elimination of senescent cells, for instance by FOXO4-DRI. In addition, exciting developments were recently reported in the field of stem cell biology, where it was shown that transient expression of the Yamanaka stem cell factors can promote tissue rejuvenation [7]. This is not yet therapeutically applicable, but most likely this will only be a matter of time.…”
Section: Le Tour De Foxo a Demanding Journey But One With Great Rewmentioning
confidence: 99%
“…As a comparison to the placebo-controlled clinical trial with the statin Atovastatin (Atorvas Fig. 3), 6 weeks of treatment at 10 mg/day dose increases HDL Cholesterol by 3.5%, which is not significantly different from the placebo increases in HDL Cholesterol of 2.3% [70]. Fig.…”
Section: Sc100+ Increases Hdl Cholesterolmentioning
confidence: 99%
“…We also identified the subset of nutraceuticals that have little or no known side effects. Finally, we focused on stem cell function as a critical factor in rejuvenation [4][5][6] by screening candidate longevity nutraceuticals for their effectiveness in stimulating and/or maintaining adult stem cell growth in human tissue culture screens. As we detail below, the final 10 herbal extracts in SC100+ provide a diverse set of bioactive compounds, which appear to act on many of the critical health and longevity pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Also, low-caloric diets, that can extend the approximate 2-year lifespan of rodents by more than 40%, extend the approximate 6-year lifespan of primates by more than 50% (see Pifferi et al 2018), without observed sign of physical nor mental health deterioration. The graft of bio-printed organs (see Ravnic et al 2017;and Mir and Nakamura 2017) and the in vivo degradation of old tissues that the body then naturally replaces by younger tissue (see Fahy 2003;Ocampo et al 2016;Mosteiro et al 2016;and Mendelsohn et al 2017) are already being tested in specific clinical settings. The latter advances show that science is not only on its way to slow down human aging but also to restore youthful characteristics to the body once old.…”
Section: Solutions Derived From Biology Of Aging Are Reaching Clinicsmentioning
confidence: 99%